The Role of Ubiquitination in TWEAK-Stimulated Signaling - Vucic, Domagoj (Frontiers in Immunology, 2013)
TNF superfamily ligands and receptors are responsible for development, immunity and homeostasis of metazoan organisms. Thus, it is not surprising that signals emanating from these receptors are tightly regulated. Binding of TWEAK to its cognate receptor, FN14, triggers the assembly of receptor-associated signaling complex, which allows the activation of canonical and noncanonical NF-κB as well as MAPK signaling pathways. Ubiquitin ligases c-IAP1 and c-IAP2 and adaptor proteins TRAF2 and TRAF3 are crucial for the regulation of TWEAK signaling as they facilitate the recruitment of distal signaling components including IKK and LUBAC complexes. At the same time c-IAP1/2, together with TRAF2 and TRAF3, promote constitutive ubiquitination and proteasomal degradation of NIK – a kinase with critical role in the activation of noncanonical NF-κB signaling. While c-IAP1/2 mediated ubiquitination allows the activation of TWEAK stimulated canonical NF-κB signaling, these E3 ligases are negative regulators of noncanonical signaling. TWEAK stimulation prompts the recruitment of c-IAP1/2 as well as TRAF2 and TRAF3 to the FN14 signaling complex leading to c-IAP1/2 autoubiquitination and degradation, which stabilizes NIK and allows subsequent phosphorylation of IKKα and partial proteasomal processing of p100 to activate gene expression. Recent studies have revealed that the spatio-temporal pattern of TWEAK stimulated ubiquitination is a carefully orchestrated process involving several substrates that are modified by different ubiquitin linkages. Understanding the significance of ubiquitination for TWEAK signaling is important for the overall understanding of TWEAK biology and for the design of therapeutics that can be used in the treatment of human pathologies that are driven by TWEAK/FN14 expression and activity.